Classification of the Zoonotic Hepatitis E Virus Genotype 3 Into Distinct Subgenotypes - Nicot, Florence; Dimeglio, Chloé; Migueres, Marion; Jeanne, Nicolas; Latour, Justine; Abravanel, Florence; Ranger, Noémie; Harter, Agnès; Dubois, Martine; Lameiras, Sonia; Baulande, Sylvain; Chapuy-Regaud, Sabine; et al. (Frontiers in Microbiology, 2021)
Hepatitis E virus (HEV) genotype 3 is the most common genotype linked to HEV infections in Europe and America. Three major clades (HEV-3.1, HEV-3.2, and HEV-3.3) have been identified but the overlaps between intra-subtype and inter-subtype p-distances make subtype classification inconsistent. Reference sequences have been proposed to facilitate communication between researchers and new putative subtypes have been identified recently. We have used the full or near full-length HEV-3 genome sequences available in the Genbank database (April 2019; n=503) and distance analyses of clades HEV-3.1 and HEV-3.2 to determine a p-distance cut-off (0.093 nt substitutions/site) in order to define subtypes. This could help to harmonize HEV-3 genotyping, facilitate molecular epidemiology studies and investigations of the biological and clinical differences between HEV-3 subtypes.